Determinación de valores normales de las hormonas T3 y T4 totales mediante del Área Metropolitana del Valle de Aburrá (2000)
ABSTRACT: The measurement of thyroid hormones in canine serum is a valuable technique for the hypothyroidism, one of the most important endocrinophathies in this species at the world. It is required to have reference values for normal animals, rather than to give any diagnosis of thyroid dysfunction. Commissioned laboratories to realize the measurement must establish its own values based on specific and sensible techniques for canine species, using a representative number of samples. Therefore, the measurement considers pathologic and non pathologic factors that affect hormones levels. This research obtained measurements for T3 and T4 levels in 340 samples of serum from 176 healthy canines, from both sexes in the city of Medellín, Colombia. For such measurement a radio-inmunoanalysis kit for canines was used. Reference values were established for both hormones, in the whole sample and three age groups. Significant differences were founded with higher values of T4 in younger animals. Animals studied had weight less that 15 Kg. However, perspectives of this work are needed to establish reference values for breeds with higher weight.